Dustproof AS (acrylonitrile-styrene) resin composition as well as preparation method and application thereof

By using branched acrylonitrile-styrene copolymer, antistatic agent and compatible agent in AS resin materials, the problem of ash accumulation after long-term operation of AS resin materials is solved, and better dynamic dust protection and mechanical properties are achieved .

CN119463374AActive Publication Date: 2025-02-18WUHAN JINFA TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411572120.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-18
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Existing AS resin materials are prone to accumulation of dust after long-term operation, resulting in decreased air supply efficiency and bacterial growth.

Method used

Branched acrylonitrile-styrene copolymer is used as the matrix resin, and antistatic agents and compatible agents are added to adjust the acrylonitrile content to improve the antistatic properties and dynamic dust resistance.

Benefits of technology

It significantly improves the dynamic dustproof effect and mechanical properties of the material, reduces dust accumulation, and extends the cleaning cycle of air conditioner fan blades.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005120750220000011
    Figure BDA0005120750220000011
  • Figure BDA0005120750220000031
    Figure BDA0005120750220000031
  • Figure BDA0005120750220000061
    Figure BDA0005120750220000061
Patent Text Reader

Abstract

The invention discloses a dustproof AS (acrylonitrile-styrene) resin composition as well as a preparation method and application thereof. The dustproof AS resin composition comprises the following components in parts by weight: 40-80 parts of a branched acrylonitrile-styrene copolymer; 20-40 parts of a reinforcing agent; 0.1 to 5 parts of a compatilizer; 14 to 24 parts of an antistatic agent; the content of branched acrylonitrile in the branched acrylonitrile-styrene copolymer is not less than 26 wt%. The composition with a good dustproof effect is obtained by adopting the branched acrylonitrile-styrene copolymer as matrix resin, adding the antistatic agent and adjusting the acrylonitrile content, and the composition is particularly suitable for being applied to air conditioner fan blades and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer material modification, and more specifically, relates to a dustproof AS resin composition and a preparation method and application thereof. Background Art

[0002] AS resin (acrylonitrile-styrene copolymer) is a thermoplastic polymer material with high strength, excellent transparency and easy processing. The styrene component makes the AS resin harder and easier to process, and the acrylonitrile component makes the AS resin have excellent chemical resistance and heat resistance. Glass fiber-modified AS resin can significantly improve the strength and rigidity of the material and reduce its linear thermal expansion coefficient, and has better dimensional stability, making it suitable for parts with high requirements for strength and dimensional stability, such as air conditioner blades, audio housings, etc. However, due to the poor compatibility between glass fiber and matrix AS resin, it will be exposed on the surface of the matrix resin, resulting in a rough surface of the fan blade material, which will accumulate dust during the long-term operation of the air conditioner, resulting in a decrease in air supply efficiency and easy breeding of bacteria.

[0003] Adding an antistatic agent to the reinforcing agent reinforced AS resin to increase the surface resistivity of the material is a common method in the industry, but this method can only help to improve static dust accumulation. For air conditioner fan blades that are in long-term operation, a large amount of dust will still accumulate on the surface of the fan blades after a period of operation. Therefore, the art needs to develop a dust-proof AS resin composition. Summary of the invention

[0004] The object of the present invention is to overcome the defect or deficiency of the prior art styrene-based composition that dust is easily accumulated in a dynamic state, and to provide a dust-proof AS resin composition.

[0005] Another object of the present invention is to provide a method for preparing the dust-proof composition.

[0006] Another object of the present invention is to provide application of the dust-proof composition.

[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0008] A dustproof AS resin composition comprises the following components calculated in parts by weight:

[0009]

[0010] The acrylonitrile content in the branched acrylonitrile-styrene copolymer is not less than 26 wt %.

[0011] The invention provides a dustproof AS resin composition. A branched acrylonitrile-styrene copolymer is used as a base resin, an antistatic agent and a compatibilizer are added, and the content of branched acrylonitrile in the base resin is adjusted to improve the antistatic property and the dynamic dustproof performance. Specifically, a high acrylonitrile content can improve the polarity of the material, the interaction between the branched acrylonitrile-styrene copolymer and the reinforcing agent is enhanced, and the exposure of the reinforcing agent is avoided. Meanwhile, the improved polarity of the branched acrylonitrile-styrene copolymer can improve the interaction among the base resin, the reinforcing agent and the antistatic agent, and play a great synergistic role. Not only can the exposure of the reinforcing agent be reduced, but the distribution of the antistatic agent in the base material can be promoted, so that the mechanical properties and the dynamic dustproof performance of the composition are greatly improved.

[0012] It should be noted that the acrylonitrile content in the branched acrylonitrile-styrene copolymer of the present invention is not less than 26wt%, for example but not limited to not less than 26wt%, 26.5wt%, 27wt.%, 27.5wt.%, 28wt.%, 28.5wt.%, 29wt.%, 29.5wt.%, 30wt.%, 30.5wt.%, 31wt.%, 31.5wt.%, 32wt.%, 32.5wt.% or 33wt.%, etc. can all achieve the present invention.

[0013] Furthermore, the acrylonitrile content in the branched acrylonitrile-styrene copolymer is 27-33 wt.%. The dustproof AS resin composition prepared within this range has better comprehensive performance.

[0014] The acrylonitrile content in the branched acrylonitrile / styrene copolymer can be characterized by infrared spectroscopy combined with nuclear magnetic resonance hydrogen spectrum and nuclear magnetic resonance carbon spectrum.

[0015] In the dustproof AS resin composition, the content of the branched acrylonitrile-styrene copolymer is preferably not less than 30 wt.%.

[0016] It should be noted that the branched acrylonitrile-styrene copolymer in the present invention can be commercially available or homemade.

[0017] Specifically, the branched acrylonitrile-styrene copolymer is prepared by the following method:

[0018] It is obtained by polymerization of styrene monomer and acrylonitrile monomer under the conditions of initiator and molecular weight regulator.

[0019] Specifically, the acrylonitrile content is adjusted by adjusting the amounts of styrene monomer and acrylonitrile monomer.

[0020] Specifically, the mass ratio of the styrene monomer to the acrylonitrile monomer is 65:35 to 74:26.

[0021] Specifically, the polymerization reaction temperature is 140-160° C., and the polymerization reaction time is 2-4 hours.

[0022] Specifically, the initiator is a tetrafunctional initiator.

[0023] Specifically, the content of the initiator and the molecular weight regulator is 0.05-0.15wt% of the total content of the styrene monomer and the acrylonitrile monomer input into the synthesis.

[0024] In some specific embodiments, the branched acrylonitrile-styrene copolymer is prepared by the following method:

[0025] Adopt high temperature continuous solution polymerization device to synthesize branched acrylonitrile-styrene copolymer, styrene monomer, acrylonitrile monomer, solvent toluene, tetrafunctional initiator (for example tetratert-butyl peroxytetracarbonate), relative molecular weight regulator TDDM are mixed and uniformly added into reactor, the reactor is heated with oil bath, the reaction temperature is 140~160 ℃, the reaction time is 2-4 hours, and the copolymer is obtained by extrusion granulation with an extruder, the extruder temperature is 200~220 ℃, and the feed rate per unit time and the discharge rate of melt pump are kept consistent to ensure that the liquid level in the reactor is constant. The acrylonitrile content is adjusted by the formula ratio of styrene and acrylonitrile. The tetrafunctional initiator and the relative molecular weight regulator content are 0.1wt% of the total content of styrene monomer and acrylonitrile monomer input into the synthesis.

[0026] Furthermore, the dustproof AS resin composition also includes 1 to 5 parts of a lubricant, and the lubricant is an amide lubricant.

[0027] Specifically, the amide lubricant includes one or more of erucamide, oleamide or N,N'-ethylenebisstearamide.

[0028] Furthermore, the dustproof AS resin composition comprises the following components calculated in parts by weight:

[0029]

[0030] Furthermore, the reinforcing agent includes one or more of glass fiber, talcum powder, wollastonite, whisker or glass microbeads. Specifically, the corresponding reinforcing agent can be selected according to the mechanical properties required for the actual application, and the dynamic dustproof effect can be achieved.

[0031] Furthermore, the reinforcing agent is glass fiber.

[0032] Furthermore, the compatibilizer includes maleic anhydride grafts and / or acrylate grafts.

[0033] Specifically, the maleic anhydride grafted product may be one or more of ABS-g-MAH, AS-g-MAH or styrene-maleic anhydride copolymer.

[0034] Specifically, the acrylic graft may be one or more of ABS-g-GMA, methyl methacrylate, and styrene-acrylonitrile-glycidyl methacrylate copolymer.

[0035] Furthermore, the antistatic agent is a polyetheresteramide copolymer and / or a polyetheresterolefin copolymer.

[0036] Furthermore, the antistatic agent is a polyetheresteramide copolymer.

[0037] Furthermore, the other auxiliary agents include one or more of antioxidants, weathering agents or color powders.

[0038] In the present invention, commonly used antioxidants can be selected according to the prior art, such as but not limited to hindered phenol antioxidants and / or phosphite antioxidants.

[0039] Specifically, the hindered phenol antioxidant is one or more of N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) (Irganox 1098), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 1010), 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (Irganox 259), β-(4-hydroxy-3,5-di-tert-butylphenyl)propionic acid n-octadecyl (Irganox 1076) or 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acrylate]-1,1-dimethyl}-2,4,8,10-tetraoxaspirocycloundecane (ADK AO-80).

[0040] The phosphite antioxidant is one or more of tris(2,4-di-tert-butylphenyl)phosphite (Irganox 168), bis(2,6-di-tert-butyl-4-tolyl) pentaerythritol phosphite (PEP-36) or 627A.

[0041] In some specific embodiments, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1: (1-3).

[0042] The present invention also protects a method for preparing the dustproof AS resin composition, comprising the following steps:

[0043] S1. The dustproof AS resin composition above except the reinforcing agent other components are mixed to obtain a premix;

[0044] S2. The premix is ​​fed through the main feeding port, and the reinforcing agent is fed through the side feeding port, and the mixture is melt-blended and extruded to obtain granules.

[0045] Specifically, a high-speed mixer is used for mixing in step S1.

[0046] Specifically, the mixing temperature is 20 to 50° C., the mixing speed is 100 to 800 rpm, and the mixing time is 2 to 5 minutes.

[0047] Furthermore, the extrusion granulation adopts a twin-screw extruder.

[0048] Specifically, the feeding speed of the twin-screw extruder is 200-350 rpm, the main engine speed is 100-500 rpm, and the vacuum degree is ≤0.1 MPa.

[0049] Specifically, the temperature of zone 1 of the twin-screw extruder is 220-250°C, the temperature of zone 2 is 220-240°C, the temperature of zone 3 is 210-220°C, the temperature of zone 4 is 210-230°C, the temperature of zone 5 is 210-230°C, and the die temperature is 220-230°C.

[0050] Specifically, the aspect ratio of the twin-screw extruder is (36-48):1.

[0051] The present invention also protects the use of the dustproof AS resin composition in preparing air conditioner fan blade materials.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] The invention provides a dustproof AS resin composition. By adopting a branched acrylonitrile-styrene copolymer as a base resin, adding an antistatic agent, and adjusting the acrylonitrile content in the branched acrylonitrile-styrene copolymer, the prepared AS resin composition can have good dynamic dustproof effect and good mechanical properties. DETAILED DESCRIPTION

[0054] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0055] The raw materials used in each embodiment and comparative example are:

[0056] 1. Raw materials and reagents

[0057] Branched acrylonitrile-styrene copolymer:

[0058] Branched acrylonitrile-styrene copolymer 1: acrylonitrile content 32wt%, homemade;

[0059] Branched acrylonitrile-styrene copolymer 2: acrylonitrile content 26wt%, homemade;

[0060] Branched acrylonitrile-styrene copolymer 3: acrylonitrile content 28wt%, homemade;

[0061] Branched acrylonitrile-styrene copolymer 4: acrylonitrile content 30wt%, homemade;

[0062] Branched acrylonitrile-styrene copolymer 5: acrylonitrile content 24wt%, homemade;

[0063] Specifically, the preparation method of the branched acrylonitrile-styrene copolymer is as follows:

[0064] The AS resin is synthesized by a high-temperature continuous solution polymerization device. The monomers styrene monomer, acrylonitrile monomer, solvent toluene, a tetrafunctional initiator (Luperox JWEB50, Arkema Company), and a relative molecular weight regulator TDDM are uniformly mixed and added to a reactor. The reactor is heated with an oil bath, the reaction temperature is 150°C, the reaction time is 3 hours, and the pellets are extruded by an extruder. The extruder temperature is 210°C. The feed amount per unit time and the discharge amount of the melt pump are kept consistent to ensure that the liquid level in the reactor remains unchanged. The acrylonitrile content is adjusted by the formula ratio of styrene and acrylonitrile. The mass ratio of the styrene monomer to the acrylonitrile monomer is 65:35 to 74:26. ​​The content of the tetrafunctional initiator and the molecular weight regulator is 0.1wt% of the total content of the styrene monomer and the acrylonitrile monomer input into the synthesis.

[0065] Acrylonitrile-styrene copolymer: SAN KFA-180, acrylonitrile content of 30wt%, purchased from Liaoning Jinfa;

[0066] Enhancer:

[0067] Reinforcement 1: glass fiber, ECS13-4.5-534, average diameter 13 μm, purchased from Jushi, China;

[0068] Reinforcement agent 2: wollastonite, WFC5 2101, purchased from Hubei Fengjiashan Silica Fiber Co., Ltd.;

[0069] Compatibilizer: styrene-maleic anhydride copolymer, SMA700, purchased from Jiaxing Huawen;

[0070] Antistatic Agent:

[0071] Antistatic agent 1: polyetheresteramide copolymer, PELECTRON AS, purchased from Sanyo Chemical;

[0072] Antistatic agent 2: polyetheresteramide copolymer, PELESTAT-6500, purchased from Sanyo Chemical;

[0073] Antistatic agent 3: polyether ester olefin copolymer, PELESTAT-230, purchased from Sanyo Chemical;

[0074] Lubricant:

[0075] Lubricant 1: erucamide, commercially available;

[0076] Lubricant 2: oleamide, commercially available;

[0077] Lubricant 3: zinc stearate, commercially available;

[0078] Other additives:

[0079] Antioxidant: a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:2, both of which are commercially available; it should be noted that the same raw materials are used in the parallel experiments of the examples of the present invention and the comparative examples.

[0080] 2. The styrene-based compositions described in the embodiments and comparative examples of the present invention are prepared according to the formulations in Tables 1 to 2 by the following method, comprising the following steps:

[0081] S1. The other components except the glass fiber were premixed in a high mixer according to the proportion, the mixing temperature was 30 ° C, the mixing speed was 500 rpm, the mixing time was 3 minutes, and the premix was uniformly mixed;

[0082] S2. The premix of step S1 is fed into a twin-screw extruder through the main feed port, and the reinforcing agent is fed through the side feed port, and the mixture is melt-blended and extruded into granules; the feeding speed of the twin-screw extruder is 275 rpm, the main engine speed is 350 rpm, and the vacuum degree is 0.08 MPa.

[0083] Specifically, the temperature of zone 1 of the twin-screw extruder is 235°C, the temperature of zone 2 is 230°C, the temperature of zone 3 is 215°C, the temperature of zone 4 is 220°C, the temperature of zone 5 is 220°C, and the die temperature is 225°C.

[0084] Specifically, the length-to-diameter ratio of the twin-screw extruder is 48:1.

[0085] 3. Performance Testing

[0086] (1) Surface resistivity measurement: The styrene-based composition in each example and comparative example was injection molded into a 3 mm*100 mm*100 mm square plate specimen, and the surface resistivity was measured according to ASTM D257-2014 standard;

[0087] (2) Determination of dynamic dustproof grade: First, prepare the crossflow fan blade. The preparation of the crossflow fan blade is to use an injection molding machine to inject the end cover, top cover, fan blade and other related parts of the crossflow fan blade. Then, the most commonly used ultrasonic welding technology in the industry is used to weld the crossflow fan blade suitable for use in the indoor unit of the air conditioner. The mass of the crossflow fan blade is 500g. After continuous operation at a speed of 800 revolutions per minute for 1000 hours, the crossflow fan blade is weighed. The weight increase of more than 2% is rated as level 4, the weight increase of 1-2% (excluding 2%) is rated as level 3, the weight increase of 0.5-1% (excluding 1%) is rated as level 2, and the weight increase of less than 0.5% (excluding 0.5%) is rated as level 1.

[0088] (3) Tensile strength measurement: The styrene-based composition in each example and comparative example was injection molded into an ISO standard dumbbell-shaped tensile specimen and tested with reference to ISO 527-1-2012 standard.

[0089] Examples 1 to 12 and Comparative Examples 1 to 3

[0090] The dosage of each component and the performance test results of the compositions in the examples and comparative examples are shown in Tables 1-2.

[0091] Table 1 Amount of each component in the dustproof AS resin composition in Examples 1 to 12 (unit: weight parts) and performance results

[0092]

[0093]

[0094] Table 2 Amount of each component in the AS resin composition in Comparative Examples 1 to 3 (unit: weight parts) and performance results

[0095]

[0096]

[0097] It can be seen from Table 1 that the dustproof AS resin composition prepared in each embodiment of the present invention has a good dynamic dustproof effect. Specifically, the dynamic dustproof grade is not higher than level 2, and the surface resistivity is not higher than 9*10 10 Ω; the dynamic dustproof level is preferably not higher than level 1, and the surface resistivity is not higher than 5*10 10 Ω, tensile strength is not less than 115MPa.

[0098] Comparison of Comparative Example 1 and Examples 1 to 4 shows that if the acrylonitrile content in the branched acrylonitrile-styrene copolymer is too low, the mechanical properties and dustproof properties of the obtained AS resin composition are reduced.

[0099] It can be seen from Comparative Example 2 that if no antistatic agent is added, the dustproof grade of the AS resin composition obtained by adding a lubricant is significantly reduced.

[0100] It can be seen from Comparative Example 3 that the dustproof grade of the AS resin composition prepared by using ordinary acrylonitrile-styrene copolymer is significantly lower than that of the embodiment.

[0101] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A dustproof AS resin composition, characterized in that The composition comprises the following components calculated by weight: The acrylonitrile content in the branched acrylonitrile-styrene copolymer is not less than 26 wt %.

2. The dustproof AS resin composition according to claim 1, characterized in that: The dustproof AS resin composition further comprises 1 to 5 parts of a lubricant, and the lubricant is an amide lubricant; preferably, the amide lubricant comprises one or more of erucamide, oleamide or N,N'-ethylenebisstearamide.

3. The dustproof AS resin composition according to claim 1, characterized in that: The composition comprises the following components calculated by weight:

4. The dustproof AS resin composition according to claim 1 or 3, characterized in that: The acrylonitrile content in the branched acrylonitrile-styrene copolymer is 27-33 wt %.

5. The dustproof AS resin composition according to claim 1 or 3, characterized in that: The branched acrylonitrile-styrene copolymer has a melt flow rate of 15 to 35 g / 10 min at 220° C. and 10 kg.

6. The dustproof AS resin composition according to claim 1 or 3, characterized in that: The reinforcing agent includes one or more of glass fiber, talcum powder, wollastonite, whisker or glass microbeads.

7. The dustproof AS resin composition according to claim 1 or 3, characterized in that: The compatibilizer includes maleic anhydride grafts and / or acrylate grafts.

8. The dustproof AS resin composition according to claim 1 or 3, characterized in that: The antistatic agent is a polyetheresteramide copolymer and / or a polyetheresterolefin copolymer.

9. A method for preparing the dustproof AS resin composition according to any one of claims 1 to 8, characterized in that: The steps include: S1. The dustproof AS resin composition according to any one of claims 1 to 8, except for the reinforcing agent, is mixed to obtain a premix; S2. The premix is ​​fed through the main feeding port, and the reinforcing agent is fed through the side feeding port, and the mixture is melt-blended and extruded to obtain granules.

10. Use of the dustproof AS resin composition according to any one of claims 1 to 8 in preparing air conditioner fan blade materials.

Citation Information

Patent Citations

  • Antimicrobial dust-proof material for air-conditioning fan and method for producing the same

    CN101130683A

  • Dustproof ABS composite material and preparation method thereof

    CN113999483A

  • AS composition as well as preparation method and application thereof

    CN118256043A